Qualitative assessment of water erosion In ait attab- the midle big Atlas – Morocoo - Bouazza, Salak; Al-Khaliki, Yahya; Jaai, Farid; Aref, Saied (Journal of natural sciences, life and applied sciences, 2018)
In this study, we will examine the qualitative assessment of water erosion in the area of Ait- Attab, we adopt GIS and ZERMOS in the first stage to study water erosion and the resulting forms, and to cope with the possible erosion as an initial stage: Field work, aerial photos and a map of possible erosion in order to complete the current erosion map and the resulting forms in the second stage. This study concluded that the area of Ait Attab is a rich ground to study water erosion in all its forms. The results showed the dominance of linear erosion, especially the cavity, at 8.55%; the spread of 63.69%, the weak erosion of 23.53%, and the rock falls by 3.52% while slips recorded 0.70%, and the banks destroyed a small percentage of 0.02%. It was also found that the topography, rock and human intervention played an important role in the distribution of erosion forms.
Keywords: Middle High Atlas; Ait Atab Depression; Water Erosion; Qualitative Evaluation of Water Erosion; Geographic Information Systems